ReqJourney: Engaging Students with a 2D Metaverse Serious Game for Software Requirements Education - Rodrigues, Claudia Susie C.; Nobre, Thiago S.; Nazareth, Vitoria; Werner, Cláudia (Journal on Interactive Systems, 2026)
Teaching Software Requirements (SR) is a critical challenge in Software Engineering education, primarily due to the subject’s theoretical nature and complexity, which often hampers student engagement. To address this, we developed and evaluated ReqJourney, a serious game implemented on the 2D metaverse platform Gather Town, designed to provide a dynamic, collaborative, and engaging learning experience for introductory SR topics, including requirements elicitation and analysis. An in-class evaluation was conducted with university students in a Software Processes course, utilizing the MEEGA+ model and pre/post-tests to assess educational effectiveness and user experience. The results demonstrate a significant improvement in student performance on the post-test and overwhelmingly positive feedback regarding the game’s engaging mechanics and collaborative design. These findings underscore the potential of ReqJourney as an innovative educational tool, proving that combining immersive gameplay within virtual environments with structured learning objectives is an effective strategy for reinforcing complex SR concepts.